S89 Identification Of Potentially Pathogenic Microorganisms By Selected Ion Flow Tube –mass Spectrometry (sift-ms). (10th November 2014) - Jackson, JM; Kim, VL; Tuck, AC; Wootton, SA; Wilkinson, TM
Abstract : Introduction: Improved targeted therapy and reduced clinical burden from respiratory bacterial infection could result from early identification of specific Potential Pathogenic Microorganisms (PPM). Sputum culture for identification usually requires several days. SIFT-MS has the potential to reduce the required incubation time by sampling the culture headspace to generate an ionic spectrum from volatile organic compounds that may be characteristic of the PPM. Additionally, these signatures may be detectable in breath taken directly from patients. This pilot study investigates the potential of SIFT-MS to identify 5PPMs, incubated separately for 24 hr. Methods: Training set : Haemophilus influenzae (HI), Moraxella catarrhalis (MC), Streptococcus pneumoniae (SP), Staphylococcus aureus (SA) and Pseudomonas aeruginosa (PA) cultures and a negative control incubated at 37 0 C on chocolate agar plates in sealed bags for 24 hr, 48 hr and 72 hr. Plates were opened for 10 min at room temperature before ionic spectra of the gas above the culture dishes in the range 15 to 200 mass units were recorded using SIFT-MS and standardised to operating conditions. Test set: the same five PPMs and a negative control were incubated in triplicate for 24 hr only and analysed as above. Results: Using the spectra generated with H3O+ ionisation, 6 ion sets were identified. The sum of ions within each set, expressed as a percentage of the total ion sum of masses 15 to 200 (excluding reagent ions) fell into ranges that, in combination, differentiated between the PPMs. This set of conditions was incorporated into an algorithm that was then applied to the test set of triplicate plates. The algorithm correctly differentiated all 24 hr plates with MC, SP, SA and PA from each other and from the negative control and HI plates with 100% accuracy. Negative control and HI could not be differentiated. Conclusion: This pilot study illustrates the potential for SIFT-MS to identify monocultures of 4 common PPMs within a short incubation time and encourages further study with a wider range of pathogens alone and in combination. Early identification of PPMs in culture, and translation to potentially detect carriage or infection with specific pathogens in breath may improve management of respiratory infections.